2007
DOI: 10.2106/jbjs.f.01214
|View full text |Cite
|
Sign up to set email alerts
|

Complex Posterior Fracture-Dislocation of the Shoulder

Abstract: Acute complex posterior fracture-dislocations of the shoulder are rare, but they occur in patients who are younger than the majority of other patients who sustain a proximal humeral fracture. The use of open reduction and internal fixation to treat these fractures is associated with a relatively low risk of postoperative complications, and the functional outcome is generally favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 50 publications
3
53
1
9
Order By: Relevance
“…Robinson separated posterior dislocations to simple dislocations and fracture-dislocations with a concomitant displaced fracture of the humeral head typically at the anatomical neck [12,13]. The 24 patients in that study underwent surgery within an average of 14 hours after referral with open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson separated posterior dislocations to simple dislocations and fracture-dislocations with a concomitant displaced fracture of the humeral head typically at the anatomical neck [12,13]. The 24 patients in that study underwent surgery within an average of 14 hours after referral with open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…In PSD with the rarer complex fractures of the proximal aspect of the humerus, there have been favourable functional results with the use of open relocation, fracture reduction and stabilisation, and adjuvant stabilisation procedure if necessary in 28 cases. [8] In these complex fracture-dislocations, the majority of the functional loss in the long-term was attributable to loss of internal rotation of the shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al, [13] in his series of 63 patients found no statistically significant difference in clinical, radiographic, and electrophysiological outcomes between the deltopectoral approach and deltoid-splitting approach while surgical treatment of proximal humeral fractures. Hepp et al, [14] in his study observed better functional results with deltopectoral approach and concluded that choice of approach affects the functional outcome in management of proximal humeral fractures. [15] However, Isiklar et al, [16] in his study observed better radiological and functional outcome with deltoid-splitting approach and recommended deltoid-splitting approach in management of AO (Arbeitsgmeinschaft fur Osteosynthesefragen) types B and C proximal humeral fractures.…”
Section: Fig 1 Deltopectoral Approach Fig 2 Deltoid Split Lateral Appmentioning
confidence: 93%